Draft Genome Sequence of Lactobacillus delbrueckii Strain #22 Isolated from a Patient with Short Bowel Syndrome and Previous d-Lactic Acidosis and Encephalopathy - Domann, Eugen (Genome Announc, 2016)
d-Lactic acidosis with associated encephalopathy caused by overgrowth of intestinal lactic acid bacteria is a rarely diagnosed neurological complication of patients with short bowel syndrome. Here, we report the draft genome sequence of Lactobacillus delbrueckii strain #22 isolated from a patient with short bowel syndrome and previous d-lactic acidosis/encephalopathy.